2003
DOI: 10.1097/00003226-200301000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Corneal Sensation, but not of Basal or Reflex Tear Secretion, With the Stage of Diabetic Retinopathy

Abstract: Both corneal sensation and total or reflex tear secretion are reduced in individuals with diabetes. The decrease in corneal sensation, but not that in each tear secretion, was correlated with the stage of diabetic retinopathy. Given that loss of corneal sensation is a manifestation of diabetic polyneuropathy, these results are consistent with the notion that both diabetic retinopathy and polyneuropathy result from a basement membrane abnormality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
71
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 26 publications
6
71
1
1
Order By: Relevance
“…[16][17][18][19][20][21][22][23][24][25][26] Some ocular manifestations of DM are associated with lachrymal gland dysfunction and have been related to dry eye. Several clinical studies have demonstrated that people with DM are more vulnerable to dry eye than healthy subjects.…”
Section: Tear Filmmentioning
confidence: 99%
See 4 more Smart Citations
“…[16][17][18][19][20][21][22][23][24][25][26] Some ocular manifestations of DM are associated with lachrymal gland dysfunction and have been related to dry eye. Several clinical studies have demonstrated that people with DM are more vulnerable to dry eye than healthy subjects.…”
Section: Tear Filmmentioning
confidence: 99%
“…[16][17][18][19] In people with DM, the most frequent and measurable alterations of the tear film function are reduced tear secretion, [16][17][18][19][20][21][22] tear film instability (tear film break-up time (TBUT)), 17,18,20,21 higher degree of conjunctival squamous metaplasia, [16][17][18]21 lower globet cell density, 17,21 and reduced corneal sensitivity. 17,19,21,22 Although the mechanisms of these changes in the ocular surface with DM are still unclear, some studies suggest that diabetic neuropathy affects the innervation of the lachrymal gland and that the fluctuation in the glycaemic control could affect the ocular surface and lachrymal gland secretory function, causing a decrease in basal tear secretion and TBUT. 17,20,21 However, other studies showed that basal tear secretion and TBUT values do not change, but total and reflex tear secretions are significantly reduced in subjects with DM, suggesting that the decreased reflex tearing is due to a diminished sensitivity in cornea and conjunctiva.…”
Section: Tear Filmmentioning
confidence: 99%
See 3 more Smart Citations